Aspek Keberlanjutan Dalam Konsep Arsitektur Biomimikri, Biomorfik Dan Arsitektur Ekologis - Yusuf, Moh; Fitriaty, Puteri; Bassaleng, Andi Jiba Rifai; Dwi Utomo, Muhammad (JURNAL RUANG / ISSN : 2085-6962, 2025)
This study explores the relationship between biomimicry, biomorphic, and ecological architecture, and aims to determine whether biomimicry and biomorphics can be categorized into ecological architecture. Biomimicry architecture mimics nature's shapes, systems, and mechanisms to create efficient and sustainable designs, while biomorphic architecture focuses more on nature-inspired organic aesthetics and forms. This study uses a descriptive-comparative approach, analyzing the basic principles of the three architectural approaches based on the theory developed by Frick (2007) about the principles of ecological architecture. The results show that biomimicry architecture is very much in line with the principles of ecological architecture, especially in terms of energy efficiency and sustainability, with a high average score. In contrast, biomorphic architecture is more aesthetically oriented and tends to meet sustainability criteria less, although it still contributes positively to the experience of the space. The study concludes that biomimicry architecture can be classified as part of ecological architecture, while biomorphic is more complementary in aesthetic aspects.